Bacilli and Agrobiotechnology - Islam, M. Tofazzal; Rahman, Mahfuz; Pandey, Piyush; Jha, Chaitanya Kumar; Aeron, Abhinav (Bacilli in Climate Resilient Agriculture and Bioprospecting, 2016)
This volume of comprehensive reviews updates our knowledge of research and commercialization of Bacillus-based products in agriculture and the environmental sector. The last couple of decades have witnessed tremendous growth of research on Bacillus species. Many of these species can produce industrial enzymes, and can act simultaneously as biofertilizers and as biopesticides inhibiting important phytopathogens. This "biocontrol" activity is now elucidated by a number of genomic and metabolomic studies. Bacillus formulations are being patented and commercialized on a regular basis. Understanding the biology, ecology and mechanism of action of these bacteria will play a role in the promotion of Bacillus-based products to support green technology in agriculture and agro-based industries.